Development of sexual health promotion package in pregnancy: The Delphi method - Shiva Alizadeh; Giti Ozgoli; Hedyeh Riazi; Hamid Alavi Majd (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The World Health Organization recommendation requires the development and use of effective, brief, clear, and evidence-based education packages to improve health-care outcomes. No comprehensive sexual health improvement package exists for the pregnancy period in the Iranian health system. This study aimed to develop a package to promote sexual health in pregnancy. MATERIALS AND METHODS: The present study is a qualitative study, which was conducted in 2019 in Tehran, Iran. Sexual health package during pregnancy was developed based on the National Institute for Health and Clinical Excellence (NICE) steps. The first step included reviewing of international guidelines, strategies, handbooks, education packages, and articles in this regard. The package was developed in the second step. In the third step, quality assessment was performed using expert opinion with the Appraisal of Guidelines for Research and Evaluation Instrument II (AGREE II) tool, and validation was performed using Delphi method. RESULTS: Package content was designed in two sections: for midwives and health-care providers and for pregnant mothers in three sessions (in each trimester of pregnancy). The quality assessment using the AGREE II guidelines revealed excellent quality (>89%). The package was validated based on expert opinion (>95%). CONCLUSION: The sexual health promotion package during pregnancy was designed with high quality and validity based on NICE steps. It is recommended, midwives be performed this designed and validated package in routine pregnancy care to promote the couple's sexual health.